(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2014)
يعرَّف النّثر الدّيوانيّ، بأنّه مجموعةٌ من الأوامر والرّسائل السّلطانيّة والبشارات والعهود، والتّواقيع وغيرها، ممّا كان يصدر عن ديوان الإنشاء باسم السّلطان، وهو على أهمّيّة بالغةٍ، تكمن في رصد الإشارات الثّقافيّة والاجتماعيّة، والمرجعيّات الدّينيّة، التي تمّ اختزالها ضمن إطار لغةٍ نثريَّة مميّزةٍ. وفي كل نص ديواني تحصل عمليّة تفاعل لغوي، بين النّسيج الّلغويّ النّصي والبنيات الّلغويّة الوافدة إليه من القرآن الكريم والسّنّة النّبويّة الشّريفة، وتتشكل تبعا لذلك مستويات لغوية متباينة تخلقها هذه العمليّة التّفاعليّة . Prose Diwani set of commands and messages Bowl Bisharat, covenants and signatures and other than it was issued by the Office of Construction as the Sultan, which is critical, is to monitor the signals of cultural, social and religious authorities, which have been reduced within the framework of the language of prose characteristic. In the text you get all the process of the interaction of language, linguistic fabric between the text and the linguistic structures expatriate him from the Koran and the Sunnah, and are shaped accordingly varying levels of linguistic created this interactive process.